Simulation of Producer Gas Combustion in a Premixed Burner for Ceramic Firing Process - Phitsanupong Punnarapong (2018)
© 2017 The Authors. Published by Elsevier Ltd. Producer gas from biomass may be used to substitute liquefied petroleum gas in ceramic firing process. Numerical simulation offers a powerful tool that can assist in ceramic kiln design, optimization and scale up of the process, saving expensive pilot works. This study aims to simulate combustion of producer gas in a premixed burner in ceramic kiln based on computational fluid dynamics. The steady-state governing equations were solved using the SIMPLE algorithm and the effect of turbulence on the mean flow field was accounted for using the RANS k-ω model. The reaction mechanism was used for combustion of producer gas as the intermediate species. For geometrical model, a 3D model for the burner was developed while an axis-symmetric model for a combustion chamber was implemented to reduce computational costs. The present model was validated and refined using results from experiments. It was found that simulated results of flow and temperature patterns were qualitatively in similar agreement to experiments. For temperature profiles, mean differences between experiments and simulation were within 1.0-7.4%.